Exploring genetic parameters and trait relationships in the F2 population of double cross hybrid of tomato (Solanum lycopersicum L.) - Shanmugabhavatharani, R; Saraswathi, T; Kavitha, M; Manivannan, N; Seenivasan, N; Harish, S (Plant Science Today, 2024)
An investigation was undertaken to examine the genetic parameters of tomato (Solanum lycopersicum L.), along with path and correlation analyses, to improve yield and quality attributes utilizing 16 quantitative and qualitative indicators in the F2 population of a double cross hybrid (H1), comprising 250 plants. The results of the investigation revealed a high coefficient of variation (both phenotypic (PCV) and genotypic (GCV)), coupled with high heritability (>95%) in traits such as average fruit weight (SFW), number of fruits/clusters (NFC) and lycopene content (LC). The selection of these traits suggests a strong potential for genetic improvement. The correlation analysis showed a strong and significant association with yield and its contributing traits, like the weight of the single fruit (0.869), followed by the height of the plant (0.843) and the number of fruits/plant (0.793). Path analysis also showed a substantial direct effect on yield from the number of fruits/plant (0.419) and weight of single fruit (0.416). This study's selection of these traits insights valuable breeding strategies for developing tomato varieties with high yield and enhanced nutritional quality.